THE IMPORTANCE OF USING FREE PARENTING TECHNOLOGY IN THE UPBRINGING OF PRESCHOOL CHILDREN - G. T. Xazratkulova; N. I. Rajabova (Galaxy International Interdisciplinary Research Journal, 2022)
It is well-known that every child is born with pure feelings. Life, the environment, and adults pollute their psyche. It is a very wrong approach to sharply assess children as smart, stupid, moral, obscene, generous, jealous, strong, weak, and each of them is a feeling that exists to some degree in the human mind. For a free parenting system, a child’s mind is not a white paper on which to write anything, as promoted in pedagogy. Every healthy child is born with a number of positive emotions, such as truth, beauty, honesty, and justice, and he demonstrates these feelings in his actions throughout his life. The technology of free education is important because it is similar to working in accordance with these natural human qualities and is aimed at improving them. Both in the pre-school system and at the school level, it is desirable that the educational process be based on absolute freedom, in accordance with the natural features, interests and capabilities of the child.